Profile of Physical Condition and Techniques of Padang Police Taekwondo Athletes - Fadila, Ivan; Adnan, Aryadie; Irawadi, Hendri; Setiawan, Yogi (Universitas Negeri Padang, 2023)
Background and aim. The problem in this research is to identify the factors causing the performance of Padang Police Taekwondo athletes to be not optimal. This study aims to determine the physical condition and techniques of Padang Police Taekwondo athletes.Methods. This research uses a descriptive statistical approach. The population consisted of 15 male and 5 female athletes from the Padang Police Dojang, with sampling conducted using the census method. The instruments included tests of aerobic endurance (15-minute run), leg muscle explosive power (standing broad jump), speed (20 m sprint), strength (push-up and sit-up tests), agility (side step test), flexibility (sit and reach test), and kicking technique (dollyo chagi test). Data were analyzed using descriptive statistics through frequency tabulation with the formula P = F/N × 100%.Results. The results show that the physical condition and technical abilities of Padang Police Taekwondo athletes across all assessment indicators are categorized as good to very good.Conclusions. Padang Police Taekwondo athletes demonstrate satisfactory physical and technical performance, although continuous evaluation and training improvement are still necessary to optimize athletic performance.